Phishing Cyber Security Threats - Trisolvena, Muhammad Nana; Saputra, Nana Handre (Jurnal Improsci, 2024)
Phishing is a growing threat in the realm of cybersecurity, where cybercriminals use various phishing techniques to steal sensitive information from individuals and organizations. In practice, phishing aims to obtain personal, account, and financial data by impersonating trusted parties through fake emails, websites, text messages, or social media. The term "phishing" comes from the word "fishing" which describes an attempt to lure prey with fake bait. The most common types of phishing include web phishing, email phishing, smishing phishing, scam phishing, blind phishing, whaling phishing, and angler phishing, each with different approaches and targets. Phishing causes losses to individual victims and significantly impacts the information and communication technology profession, including loss of data, reputation, security, time, cost, quality, and trust. An in-depth understanding of the types of phishing, their impacts, and their prevention and countermeasures is essential to protect yourself and your organization from phishing attacks. Therefore, awareness and education about phishing are key in building resilience to this cyber threat. As such, further research and proactive actions are needed to tackle phishing effectively in the ever-evolving digital age.